2011
DOI: 10.1186/1556-276x-6-95
|View full text |Cite
|
Sign up to set email alerts
|

A novel mechanical cleavage method for synthesizing few-layer graphenes

Abstract: A novel method to synthesize few layer graphene from bulk graphite by mechanical cleavage is presented here. The method involves the use of an ultrasharp single crystal diamond wedge to cleave a highly ordered pyrolytic graphite sample to generate the graphene layers. Cleaving is aided by the use of ultrasonic oscillations along the wedge. Characterization of the obtained layers shows that the process is able to synthesize graphene layers with an area of a few micrometers. Application of oscillation enhances t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
62
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(65 citation statements)
references
References 26 publications
1
62
0
Order By: Relevance
“…Generally, Gr or reduced graphene oxide (rGO) are used for sensor applications . Gr can be obtained from graphite by mechanical cleavage (Jayasena and Subbiah, 2011), chemical exfoliation , thermal decomposition (Wang et al, 2012), or electrochemical exfoliation (Low et al, 2013). Among other methods, electrochemical exfoliation of graphite electrode is considered a simple, rapid, and "green" method, as the use of toxic or corrosive reducing reagents or stabilizers are avoided in this method (Su et al, 2011;Singh et al, 2012;Chang et al, 2013;Gee et al, 2013;Mao et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Generally, Gr or reduced graphene oxide (rGO) are used for sensor applications . Gr can be obtained from graphite by mechanical cleavage (Jayasena and Subbiah, 2011), chemical exfoliation , thermal decomposition (Wang et al, 2012), or electrochemical exfoliation (Low et al, 2013). Among other methods, electrochemical exfoliation of graphite electrode is considered a simple, rapid, and "green" method, as the use of toxic or corrosive reducing reagents or stabilizers are avoided in this method (Su et al, 2011;Singh et al, 2012;Chang et al, 2013;Gee et al, 2013;Mao et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The essential electronic properties can be drastically changed by the layer number [35][36][37], stacking configuration [37][38][39][40][41][42], magnetic field [43,44], electric field [45][46][47], dopping [48,49], mechanical strain [50][51][52], and temperature variation [53,54]. Few-and multi-layer graphenes have been successfully produced by experimental methods such as exfoliation of highly orientated pyrolytic graphite [55][56][57][58], metalorganic chemical vapour deposition (MOCVD) [61][62][63][64][65][66], chemical and electrochemical reduction of graphene oxide [67][68][69], and arc discharge [70,71]. There exist important stacking configurations, including AAB [57,58,69], ABC [59,60,[66][67][68][69], AAA …”
Section: Introductionmentioning
confidence: 99%
“…This method is a prime example of the top-down approach towards graphene synthesis since, in this method, ultrasonic energy is used to separate graphene layers stacked together in a precursor. But this method requires a large amount of energy since sonication is the only energy source and it can be a concern, while scaling up this method [27]. Also, removal of impurities is a problem that occurs in this process.…”
Section: Sonicationmentioning
confidence: 99%
“…Jayasena et al [27] reported another approach towards mechanical exfoliation which used a diamond wedge to literally scrape off graphene from a graphite source (highly ordered pyrolitic graphite, so-called HOPG), aided by ultrasonic oscillations. This, in principle, shares the same ideology as the approach observed by Geim et al, where layers of graphene are mechanically removed from the carbon source.…”
Section: Synthesis Of Graphenementioning
confidence: 99%